1999
DOI: 10.1016/s0960-9822(99)80485-0
|View full text |Cite
|
Sign up to set email alerts
|

A role for the extraembryonic yolk syncytial layer in patterning the zebrafish embryo suggested by properties of the hex gene

Abstract: Recent studies in mouse suggest that the extraembryonic endoderm has an important role in early embryonic patterning [1]. To analyze whether similar mechanisms operate in other vertebrates, we cloned the zebrafish homologue of Hex, a homeobox gene that is expressed asymmetrically in the mouse visceral endoderm [2]. Early expression of zebrafish hex is restricted to the dorsal portion of the yolk syncytial layer (YSL), an extraembryonic tissue. By the onset of gastrulation, hex is expressed in the entire dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 37 publications
0
85
1
Order By: Relevance
“…Table 1B). Furthermore, a significant effect on chirality was also seen with selective knock-down hhex activity in the YSL (Table 1C), an extraembryonic tissue (Ho et al, 1999;Kimmel et al, 1985). In contrast, knock-down of YSL hhex activity had no effect on liver development (not shown).…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Table 1B). Furthermore, a significant effect on chirality was also seen with selective knock-down hhex activity in the YSL (Table 1C), an extraembryonic tissue (Ho et al, 1999;Kimmel et al, 1985). In contrast, knock-down of YSL hhex activity had no effect on liver development (not shown).…”
mentioning
confidence: 90%
“…Roles for hhex in embryonic and forebrain patterning (Brickman et al, 2000;Martinez Barbera et al, 2000), and thyroid (Martinez Barbera et al, 2000), and hematopoietic (Keng et al, 2000) development have been described. hhex appears to function as a transcriptional repressor in early development (Brickman et al, 2000;Ho et al, 1999;Tanaka et al, 1999), although recent data suggest it also functions as a transcriptional activator (Denson et al, 2000). Zebrafish hhex is first expressed in the yolk syncytial layer (YSL), an extraembryonic tissue that forms before the onset of gastrulation (Chin et al, 2000;Ho et al, 1999).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that endodermal induction in the extraembryonic region takes place in a very short time window, probably just before gastrulation. The extraembryonic yolk syncytial layer (YSL) in zebrafish is believed to be equivalent to mouse visceral endoderm (Ho et al, 1999) and is reported to have important roles in germ layer patterning in zebrafish and is required for the formation of ventrolateral mesendoderm and induction of the nodal-related genes in the ventrolateral marginal blastomeres (Chen and Kimelman, 2000). While the casanova gene is strongly reduced in the embryo proper, it is normally expressed or up-regulated in the extraembryonic YSL in zebrafish endodermal mutants casanova, bonnie and clyde, and faust (Kikuchi et al, 2001).…”
Section: Molecular Pathways Involved In Hemangioblast Developmentmentioning
confidence: 99%